Functional protease profiling with reporter peptides in serum specimens of colorectal cancer patients: demonstration of its routine diagnostic applicability - Findeisen, Peter; Costina, Victor; Yepes, Diego; Hofheinz, Ralf-Dieter; Neumaier, Michael (Journal of experimental & clinical cancer research, 2012)
The progression of many solid tumors is characterized by the release of tumor-associated proteases and the detection of tumor specific proteolytic activity in serum specimens is a promising diagnostic tool in oncology. Here we describe a mass spectrometry-based functional proteomic profiling approach that tracks the ex-vivo degradation of a synthetic endoprotease substrate in serum specimens of colorectal tumor patients.